KEDUDUKAN HUKUM PT SINARMAS ASSET MANAGEMENT SELAKU PEMEGANG OBLIGASI TERHADAP PT TIGA PILAR SEJAHTERA FOOD TBK DALAM PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG (STUDI KASUS NO 121/PDT.SUS-PKPU/2018/PN.NIAGA.JKT.PST) - Oktabiani, Andiya; Anggraini, Anna Maria Tri (Fakultas Hukum Universitas Trisakti, 2023)
The existence and emergence of bankruptcy law in Indonesia began due to the monetary crisis in 1997 which caused difficulties among the business world in carrying out their activities. One of them is the rules regarding bankruptcy and the rules regarding Postponement of Debt Payment Obligations (PKPU). As the main problem in this thesis, 1) What is the legal position of bond holders in Postponement of Debt Payment Obligations (PKPU) according to Law Number 37 of 2004 concerning Bankruptcy and PKPU? and 2) Are the judge's considerations in Case Decision No.121/Pdt.Sus-PKPU/2018/PN.Niaga.Jkt.Pst in accordance with UUK-PKPU No. 37 of 2004 and Law No. 8 of 1995. This research uses a descriptive type of normative legal research using secondary data, then analyzed qualitatively with a deductive mindset as a way of drawing conclusions. The results of the research show that 1) if indeed the actions of creditor bond holders acting alone without being represented by a Trustee are not justified by the Capital Markets law, considering that the offering of bonds is usually purchased by creditors in large quantities. 2) Creditors holding bonds are concurrent creditors, because based on Articles 1131 and 1132 of the Civil Code, one of the privileges of creditors in terms of debt repayment is the existence of a guarantee.